The International and Political Journal: The New Middle East in the Perspective of US Strategy (Constants and Variables) - Al-Rufaie, Lecturer.Dr. Ali Mohammed Amneef (The International and Political Journal, 2024)
Despite what has been said and said that the status of the Middle East has declined in American accounts in light of international changes. However, whatever is said in this regard, the region is still and will remain a region of conflict and influence that enjoys a great deal of strategic importance in the American strategic perception. Therefore, the proposal of the new regionalism project in the Middle East is now based on the ruins of political, economic, and cultural-civilizational strategic variables that the American strategy has been keen to absorb. The fixed ones. In light of the rise of China, which began to pose a real challenge to the United States of America and its dominance on the international scene, and then the Russian-Ukrainian war, which began to expand and threaten to use nuclear weapons, the Israeli war on Gaza after the events of October 7 The entry of Iran and Hezbollah into Lebanon in this war took a decade and brought the Middle East back to the forefront again.